Design of Network Service Transmission with LDPC Coding in Space Laser Communication - ZHANG Xiaole; TAN Xiaochuan; LI Zhe (Guangtongxin yanjiu)
【Objective】Affected by factors such as atmospheric attenuation and atmospheric turbulence, wireless laser communication will produce a certain degree of bit error, and it is often necessary to add error correction codes to improve the signal transmission quality. Low Density Parity Check codes (LDPC) have performance close to the Shannon's limit, and their error-correcting ability will increase significantly with the increase of codeword length. For codes with a large length of information segment, when each code corresponds to an Ethernet frame, its encoding efficiency will be seriously affected. Designing the transmission method for Ethernet frames in a way that allows both different speeds and lengths of Ethernet frames to fully leverage the encoding and decoding efficiency is crucial for enhancing the transmission rate of Ethernet data sources.【Methods】Based on the LDPC (4 050, 2 700) encoding with a data bit width of 16 bit, this paper designs a gigabit network service transmission method. The functions of each module are clearly divided, and the state machine is used in the design of the module. Therefore, the problems in the design process can be quickly located, and the development efficiency is very high. Setting an appropriate operational cycle at the transmitting end to process Ethernet frames, through operations such as framing, packet assembly, and filling with random sequences, enables Ethernet traffic of different frame lengths and rates to adaptively match the information segment length of the LDPC encoding module, thereby fully utilizing the efficiency of LDPC encoding. Each Ethernet frame can be finally recovered by deframing at the receiving end.【Results】Finally, this article verified the design scheme on the Field Programmable Gate Array (FPGA) board of XILINX, and tested the transmission rate of Ethernet data with different frame lengths by using a gigabit network tester. The results show that the data rate can reach the limit rate of 1 Gbit/s. Afterwards, different services such as video and files are successfully tested.【Conclusion】The article proposes an Ethernet service transmission method specifically designed for scenarios where the information segment length exceeds the Ethernet frame length, enabling it to accommodate Ethernet data transmission with varying lengths, rates, and types of services. The efficiency of the encoding module can be fully utilized to meet the demand for high-speed Gigabit Ethernet service transmission in wireless laser communication.